Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

if f(x) = x 2 – 1 and g(x) = 3x + 1, then g(f(x)) = ?

if f(x) = x2 – 1 and g(x) = 3x + 1, then g(f(x)) = ?

Grade:12

1 Answers

Arun
25763 Points
3 years ago
g(f(x)) will be =  3(x2 –1)+1
thus g(f(x)) = 3x2 –3 +1
 = 3x2 –2 (Answer)
Note- in these type of questions, just see that g(x) is a function of f(x)
thus f(x) should be put in place of x in g(x)
Hope it helps

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free